PHOTOGRAPHY CLICHÉS: ON BAUDELAIRE’S MEDIA AESTHETICS AND THE MECHANICAL ARTS - Grøtta, Marit (The Nordic Journal of Aesthetics, 2017)
The aim of this article is two-folded. First, I wish to situate Baudelaire in the midst of 19th-century media, bring attention to the way he explored the new media of his day, and suggest that he developed his own media aesthetics. Second, I wish to examine Baudelaire’s relation to photography more specifically, emphasizing his love of commonplaces and clichés. I begin by contextualizing Baudelaire’s notorious attack on photography in the Salon de 1859 and then examine three poems in light of the photographic culture of Baudelaire’s day. Central here is the experiment on the notion of identity that was carried out with the spread of portrait photography: the notation of a unique identity was undermined, processes of multiplication were explored, and the poetic discourse of the “soul” was radically changed.